Cultural Subordination and Nomadic Subjectivity: A Posthumanist Critique of Casteism in Perumal Murugan’s Seasons of the Palm - Agnes Jeba S (ILN Journal: Indian Literary Narratives, 2025)
The apparatus pattern of class consciousness plays a universal role in cultural subordination. In rural Tamil Nadu, the class dimension is ascribed in terms of casteism, subjugating marginalised communities in mental, physical, and moral aspects. Perumal Murugan, a realistic Tamil writer, efficaciously displays the hegemonic influence of landowners over subordinate labourers, especially child labourers. Murugan, through his novel, Seasons of the Palm, attempts to expose the embedded violence against untouchables or subordinates within the hierarchical spectrum by giving life to characters like Shorty and his fellow sheep-herd child labourers, who work as slaves to their masters. The research paper is infused with the standpoint of posthumanism theory, a call to the quest for logical cultural homogeneity of humanism attained through a ‘zoe-centred’ ethical approach. The theoretical premise of posthumanism embodies a pivotal role in defeating the inhumane and violent cultural ideology that prevails consciously in the traditional mentality of so-called ‘upper-caste’ people in Tamil rural society. The research paper emphasises the nomadic nature of a constructive society based on the radical critique concept of ‘Nomadic Subjectivity’, which rhetorically rejects the fixed hierarchical idea of a superior human, transcending authenticity from ‘being to becoming’.